Penerapan Model Pembelajaran Edutainment Dalam Meningkatkan Hasil Belajar Siswa Di MTsN 1 Kota Makassar - R, Mukhlisah; Mustamin, Mustamin; Azhar, Muh (LP2M Universitas Islam Ahmad Dahlan, 2025)
This research examines the application of the edutainment learning model to improve the learning achievement of grade IX Science students in the subject of Cultural History at MTsN 1 Makassar City. The Classroom Action Research (CAR) implemented consisted of two cycles, each consisting of two meetings, involving 30 research subjects. Data were collected through observation, interviews, tests, and documentation, then analyzed using percentage and average (Mean) calculations. The results of the study showed a significant increase in student learning achievement between cycles. In cycle I, 20 students achieved learning completion with an average score of 74.6 (